Analiza wybranych podręczników do nauczania języka polskiego jako obcego w kontekście edukacji seniorów - Fiema, Mariola; Janowska, Iwona (Neofilolog, 2017)
The main aim of the article is to direct attention towards the specific educational needs of elderly people who are learning a foreign language. One of the main points of this paper is to describe seniors and present biological, psychological, cultural and social factors that affect their SLA (Second Language Acquisition) process. Course books used for the process of learning Polish as a foreign language have also been analyzed on the basis of their usefulness for seniors. The analysis of the course books was conducted on the basis of specially prepared criteria for the evaluation of language teaching materials.